RETURN ON EQUITY HAS AN EFFECT ON DEBT TO EQUITY RATIO AND WORKING CAPITAL TURNOVER OF PROPERTY AND REAL ESTATE SUB-SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) PERIOD 2018-2022 - Yono Maulana Maulana; Maya Sari; Mega Yusdian Puteri (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study aims to determine